Sociocultural aspects of schistosomiasis mansoni in an endemic area in Minas Gerais, Brazil - Andréa Gazzinelli; Maria Flávia Gazzinelli; Matilde Miranda Cadete; Samuel Pena Filho; Ilcéia Ribeiro Sá; Helmut Kloos
A study to determine the sociocultural factors influencing knowledge, attitudes, and practices of individuals from a small community toward Schistosoma mansoni infection was carried out in an endemic area in the State of Minas Gerais, Brazil. The study used qualitative approaches to collect data from school-aged children and teachers. Specific findings were that the individuals interviewed were aware of the disease, but also held inaccurate popular beliefs about transmission. Misconceptions coexisted with accurate knowledge both in children and teachers. The disease was not seen as a major health problem and did not affect their activities since it did not cause severe symptoms in most of the individuals. Although the majority of the participants related transmission to water and lack of sanitation, they did not take any preventive measures since their subsistence is highly dependent on irrigation, farming, fishing, and other essential work that is directly related to water activities. The authors discuss the development of a health education program based on the knowledge and perception of individuals about the disease and its determinants as being important for the context and behavioral change.